[μ-2,3,5,6-Tetrakis(2-pyridyl)pyrazine-κ6N6,N1,N2:N3,N4,N5]bis[diaqua(dihydrogen m-phenylenediphosphonato-κO)nickel(II)] dihydrate - Paul DeBurgomaster; Jon Zubieta (Acta Crystallographica Section E, 2010)
The title compound [Ni2(C6H6O6P2)2(C24H16N6)(H2O)4]·2H2O or [Ni2(tpyprz)(1,3-HO3PC6H4PO3H)2(H2O)4]·2H2O [tpyprz = tetrakis(2-pyridyl)pyrazine, C24H16N6] is a binuclear complex with a crystallographic inversion center located at the center of the pyrazine ring. The equivalent nickel(II) sites exhibit a distorted NiO3N3 octahedral coordination, with the three nitrogen donors of each terminus of the tpyprz ligand in a meridional orientation. An aqua ligand occupies the position trans to the pyrazine nitrogen donor, while the second aqua ligand is trans to the oxygen donor of the dihydrogen-1,3-phenyldiphosphonate ligand. The Ni—O and Ni—N bond lengths fall in the range 2.011 (3) to 2.089 (3) Å. The protonation sites on the organophosphonate ligand are evident in the significantly longer P—O bonds compared to the unprotonated sites. In the crystal structure, the complex molecules and the solvent water molecules are linked into a three-dimensional hydrogen-bonded framework through O—H...O interactions between the aqua ligands, the protonated organophosphonate oxygen atoms and the water molecules of crystallization. Intramolecular π-stacking between the phenyl group of the phosphonate ligand and a pyridyl group of the tpyprz ligand, at a distance of 3.244 (5) Å between ring centroids, is also observed.